A Secular Decline in Capital Productivity in G7 Countries - Kristina Morkunaite (Intereconomics, 2019)
There is a commonly held notion that higher fixed investment allows one to have it all — a higher labour productivity, a higher wage growth and higher or at least sustained returns on capital. However, experience shows that capital accumulation has led to a decline in total capital productivity with resulting pressures on capital returns — which have been largely offset by keeping wage growth subdued. This suggests that more policy focus should instead be placed on investment aimed at boosting total factor productivity through innovation and diffusion of technological progress so that gains in productivity and remuneration may be felt by both labour and capital.
Keywords: 330